2012
DOI: 10.1603/en11172
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Evolution of Resistance byMaruca vitrata(Lepidoptera: Crambidae) to Transgenic Insecticidal Cowpea in Africa

Abstract: We created a detailed model of the Maruca vitrata (F.) and cowpea [Vigna unguiculata (L.) Walp] system to study the possible evolution of resistance by the insect to transgenic insecticidal cowpea, which is under development. We focused on population dynamics and genetics in a region of west Africa. We simulated single-toxin and pyramided (two-toxin) cowpea and emphasized conservative, worst-case scenarios in our analysis. The results indicate that as long as a pyramided, transgenic cowpea can be developed, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 39 publications
(30 reference statements)
0
6
0
1
Order By: Relevance
“…This has potentially broad implications for insect resistance management (IRM) plans for trangennic Bt cowpea useful in the control of M. vitrata. Such mixing of M. vitrata populations with wild alternative hosts has positive implications for an IRM plan in West Africa that relies at least partially on the presence of the wild alternative hosts near fields of Bt transgenic cowpeas (Onstad et al 2012).…”
Section: Molecular Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…This has potentially broad implications for insect resistance management (IRM) plans for trangennic Bt cowpea useful in the control of M. vitrata. Such mixing of M. vitrata populations with wild alternative hosts has positive implications for an IRM plan in West Africa that relies at least partially on the presence of the wild alternative hosts near fields of Bt transgenic cowpeas (Onstad et al 2012).…”
Section: Molecular Characterizationmentioning
confidence: 99%
“…Also needed was a comprehensive list of all the non-target arthropods (especially beneficial organisms) associated with cultivated cowpea to allow an assessment of potential harm that might result from the Bt toxin. Regarding IRM, Onstad et al (2012) concluded that if Bt cowpea is deployed only into regions where M. vitrata is not endemic, i.e. northern Nigeria, then there is little concern with resistance emerging in the M. vitrata population.…”
Section: Further Research Needsmentioning
confidence: 99%
“…Endemic M. vitrata emigrates from this humid zone to cowpea-cropping areas in the north following the intertropical convergence zone. In the arid northern Sahelian Savanna, where the dry season typically lasts 7 to 8 months, the number of alternative hosts diminishes rapidly and M. vitrata occurs only as a seasonal migratory pest during the rainy season and generally becomes locally extinct (Bottenberg et al 1997;Ba et al 2009;Margam et al 2011a, b;Onstad et al 2012). There is a middle zone between the humid south and the arid north where a patchwork of M. vitrata populations exist on alternative hosts plants, especially along rivers.…”
Section: Biology and Ecologymentioning
confidence: 99%
“…Seed saving and weed management can complicate or worsen attempts to manage resistance ( Krupke et al 2009 , Onstad et al 2012 ). For the purposes of this paper and IRM, seed saving means that a farmer collects seed from insecticidal and refuge crops at the end of a growing season and plants them either separately or mixed together in the next season.…”
Section: Farmer Behaviormentioning
confidence: 99%
“…Thus, accidental blending may occur. More importantly, the dose of insecticide expressed in the crop may not be consistent in the next season ( Onstad et al 2012 ). When seeds of an insecticidal corn crop germinate in the next season and produce weedy or volunteer corn because they are not removed, the weedy corn plants may cause problems for IRM ( Krupke et al 2009 ).…”
Section: Farmer Behaviormentioning
confidence: 99%